2018
DOI: 10.1021/acs.jnatprod.8b00374
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor Erythroid 2-Related Factor 2 Activating Triterpenoid Saponins from Camellia japonica Roots

Abstract: Oxidative stress due to the presence of excess reactive oxygen species may cause cancers, aging, and many other conditions. Nuclear factor erythroid 2-related factor 2 (Nrf2) may control abnormal oxidative stress as a transcription factor by inducing antioxidant-related genes via antioxidant response elements (AREs) in the gene promoters. The 11 triterpenoid saponins (1–11) isolated from Camellia japonica roots were tested for ARE-luciferase activity and Nrf2 accumulation in human keratinocytes (HaCaT cells). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In the previous study, we isolated eleven triterpenoidal saponins and evaluated ARE luciferase activities by Nrf2 accumulation in the nucleus [ 35 ]. The chemical profile of eleven triterpenoidal saponins in CJRE were analyzed by the retention times and mass fragment patterns with the responding chemical standards ( Supplementary Figures S1 and S2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the previous study, we isolated eleven triterpenoidal saponins and evaluated ARE luciferase activities by Nrf2 accumulation in the nucleus [ 35 ]. The chemical profile of eleven triterpenoidal saponins in CJRE were analyzed by the retention times and mass fragment patterns with the responding chemical standards ( Supplementary Figures S1 and S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Here, CJRE potentiated the increase of NRF2 in the nucleus, resulting in the induction of NRF2 target genes, such as HO-1 and NQO-1, via ARE motifs in HeLa cells; CJRE potentiated the increase of NRF2 in the nucleus, resulting in the induction of its target genes, such as HO-1 and NQO-1, via ARE motifs in HeLa cells. In our previous report, some saponins isolated from C. japonica roots showed weak NRF2 induction [ 35 ]; however, it is necessary to investigate NRF2 activity using crude extracts for other purposes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NOX2 is widespread in phagocytes and tissues where it can be activated to induce increased ROS and is one of the major sources of ROS [ 38 ]. A previous study found that Nrf2 improves abnormal oxidative stress by increasing the expression of antioxidant-related genes [ 39 ]. GSTO2 can affect the expression of corresponding active proteins by changing the transcriptional activity of related genes, thereby regulating the activity of related antioxidant enzymes and reducing the negative effects of oxidative stress [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The NMR tube degradation method was performed for the absolute configuration determination of monosaccharides as described previously [22] . The absolute configurations of the constituent monosaccharide moieties of compounds 1 – 4 were determined with a literature procedure [23] …”
Section: Methodsmentioning
confidence: 99%